2022
DOI: 10.1016/j.dsx.2022.102424
|View full text |Cite
|
Sign up to set email alerts
|

Humoral antibody kinetics with ChAdOx1-nCOV (Covishield™) and BBV-152 (Covaxin™) vaccine among Indian Healthcare workers: A 6-month longitudinal cross-sectional Coronavirus Vaccine-induced antibody titre (COVAT) study

Abstract: Background and aims There is limited data available on longitudinal humoral antibody dynamics following two doses of ChAdOx1-nCOV (Covishield™) and BBV-152 (Covaxin™) vaccine against SARS-CoV-2 among Indians. Methods We conducted a 6-month longitudinal study in vaccinated healthcare workers by serially measuring quantitative anti-spike antibody at 3-weeks, 3-months and 6-months after the completion of second dose. Geometric mean titer (GMT) and linear mixed models were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…However, more than 75% of all participants followed up 6 months post second dose still had detectable neutralizing antibody responses to the homologous vaccine SARS-CoV-2 strain (D614G). Another study, comparing COVAXIN ® with Covishield also showed that there was significant decline in antibody titers in Covishield recipients compared to COVAXIN ® recipients at 6-months 21 . Further, 28 days after a booster dose of BBV152 there was a marked increase in titers to higher levels than those achieved after the two-dose primary series.…”
Section: Discussionmentioning
confidence: 95%
“…However, more than 75% of all participants followed up 6 months post second dose still had detectable neutralizing antibody responses to the homologous vaccine SARS-CoV-2 strain (D614G). Another study, comparing COVAXIN ® with Covishield also showed that there was significant decline in antibody titers in Covishield recipients compared to COVAXIN ® recipients at 6-months 21 . Further, 28 days after a booster dose of BBV152 there was a marked increase in titers to higher levels than those achieved after the two-dose primary series.…”
Section: Discussionmentioning
confidence: 95%
“…also reported a slightly higher breakthrough infection rate with Covaxin compared to Covishield ( 29 ). However, in the COVAT follow-up studies, breakthrough infection rates were similar for the two vaccines ( 30 ). Incidence rates varied from the high values reported by the Iranian study to the much lower values of 0.57% reported by Basavaraja et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the declines in peak values were just as rapid, so that by the end of 6 months post the second dose, there was a narrowing of the Ab titer gap between the two vaccines. While Covishield showed a peak of almost 100% seropositivity 3 weeks after the second dose, Covaxin showed peak seropositivity of less than 80% ( 30 ). Dash et al.…”
Section: Discussionmentioning
confidence: 99%
“…Both vaccines showed 5.6 fold decrease in seropositivity rate at 6-month. [27] Chakraborty et al evaluated AEFEs in a study conducted over four months at a select apartment in White eld, Bangalore, India. Researchers found a signi cantly higher number of adverse effects after the rst dose of vaccine A when compared with vaccine B (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies compared the immunogenic and reactogenic e cacy of vaccines. [13][14][15] The present study compared two vaccines on adverse effects follow immunization (AEFIs) and COVID-19 related outcomes, including the incidence of COVID-19 post-immunization, symptoms, and their severity, hospital admissions, and CT ndings.…”
Section: Introductionmentioning
confidence: 99%